ARKS AT SEA AND ARCS OF TIME - Connolly, William E. (Homo Mimeticus II, 2024)
"Yahweh looked upon the human, saw him growing monstrous in the land—desire created only bad thoughts, spreading into his acts. Now Yahweh’s pain was hard… ‘I will erase the earthlings I have created from the face of the earth,’ said Yahweh, ‘from human creature to wild beast, to bird in the air—it chills me to have made them.’ But innocent Noah warmed Yahweh’s heart" (Rosenberg and Bloom 1990, 69).¹ The story of innocent Noah, and the ark he built amidst the corruption surrounding him, is familiar to everyone touched by Jewish, Muslim, or Christian religions. Similar stories of